Keadilan dalam Produksi: Tinjauan Literatur tentang Implementasi Prinsip Keadilan dalam Ekonomi Islam - Maghfira, Inaya Hikma (Maliki Interdisciplinary Journal, 2025)
This research examines the application of the principle of production justice in the context of Islamic economics, which emphasizes the fair distribution of wealth and the protection of workers' rights. Justice in the Islamic economy is implemented through zakat, infaq, waqf, and the prohibition of labor exploitation and usury. Using a systematic literature review method, this study analyzes key themes such as fairness in profit sharing, wages, and working conditions. Results show that while the principle of justice is enshrined in sharia, its implementation is still hampered by weak regulation and supervision. Some communities have successfully implemented it on a small scale, but further steps are needed for wider implementation for the welfare of the community.